تعليم وتعلم اللغة العربية بمركز اللغة العربية بولاية سلانجور - ماليزيا = Teaching and learning Arabic at Selangor Arabic centre - Febrian, Dedek; Lubis, Maimun Aqsha; Md Yasim, Irma Martiny; AlOsman, Abdulrahman; Sjahrony, Aisyah (ASEAN, 2017)
Language is a system of words that particular people use to express their thoughts and feelings. The Arabic language is words that Arabs use to express their purposes. Thus, learning Arabic became a prerequisite for understanding the Holy Quran and the prophetic traditions. It and Islam concurrently came to Malaysia via Arab traders. It has been a tool of communication, a mediator of connection between the child and his environment, and also as a medium of learning religious sciences, moreover it has been used by universities, institutes, colleges, schools, and centres of learning. The teaching and learning of Arabic language in Malaysia have been under supervision of three official bodies which are Ministry of Education refers to Malaysian federal government, department of Islamic affair refers to state government (both are governmental administration), and also non-government organisation (private). The department of Islamic affair Selangor state intentionally established a centre of Arabic language as the basis of state Arabic centre in order to serve Islam and to advance the teaching and learning the language of the Holy Quran. The study was aimed to discover the programs and activities of Selangor Arabic Centre (SAC) with their method of practice and syllabus of teaching and learning Arabic for the targeted group of people such as teachers, students, administrative employee, government institution or otherwise, and the public during the course. Furthermore, the objective of this study was also pointed to determine the development of the syllabus for teaching Arabic, Arabic camps, the workshop which is guiding to develop of teaching and learning Arabic. The study employed a qualitative research design. To collect the information and data, the researchers were using written documentation and employing the descriptive-inductive method to analyse the data. From the finding of the study, it was discovered that syllabus of teaching and learning Arabic utilised by SAC is based on communication skill, whereas the approaches communicative approaches to make the learners be able to communicate in required language. SAC has been using selective methods appropriate to the condition to thrill the targeted group of leaners. Based on the textbooks utilised by SAC, indicated that the materials; consist of four language skills and language science. The applied method in teaching and learning Arabic is the best modern method through language activities either indoor or outdoor with the newest techniques and aided computer programs.